A new energy efficient process for hydrogen purification using ZIF-8/glycol–water slurry: Experimental study and process modeling. (13th September 2021) - Peng, Xiaowan; Jia, Chongzhi; Qiao, Zhichao; Yang, Shaowu; Liu, Bei; Deng, Chun; Li, Hai; Chen, Wan; Sun, Changyu; Chen, Guangjin
Abstract: Effective recovery of hydrogen from refinery off-gas and coke oven gas, in which hydrogen and methane are key components, is increasingly important for the development of hydrogen energy. In this paper, we introduced a new energy efficient process for hydrogen purification from CH4 /H2 mixture. Firstly, we conducted a phase equilibrium experimental study for CH4 /H2 in zeolitic imidazolate framework-8 (ZIF-8)/glycol–water slurry. The simple absorption and desorption configuration is adopted for the continuous separation of CH4 /H2 using ZIF-8/glycol–water slurry. The multi-stage pseudo-absorption modeling approach was introduced for the modeling and simulation of the absorption–adsorption and desorption columns via using multiple flash modules in Aspen Plus. The binary interaction parameters in the thermodynamic model were fitted by experimental data within an acceptable error (4.93%). The operating conditions (i.e., the number of theoretical stages, feed stage, flash pressure, and desorption pressure) were determined to increase H2 concentration in product and H2 recovery ratio. The energy performance of the process was also evaluated. Given the feed gas contains 50 mol% H2, the gas–slurry volume ratio of 43.27 is required to produce 95 mol% H2 with a high recovery of 97.94%. The total energy consumption per unit volume of product is 0.06254 kW·h/Nm 3 . Results indicate that the hybrid absorption-adsorption process is a promising energy efficient technique to separate CH4 /H2 in the future. Graphical abstract: Image 1 Highlights: ZIF-8/glycol–water slurry was experimentally effective for the separation of CH4 /H2 . Use multi-stage pseudo-absorption model to simulate absorption–adsorption column. Total energy consumption per unit volume of product is only 0.06254 kW·h/Nm 3 . New process can produce hydrogen of 95 mol% with high hydrogen recovery of 97.94%.